2017
DOI: 10.1002/pca.2702
|View full text |Cite
|
Sign up to set email alerts
|

Integrating High-Resolution and Solid-State Magic Angle Spinning NMR Spectroscopy and a Transcriptomic Analysis of Soybean Tissues in Response to Water Deficiency

Abstract: The integration of the H HR-MAS and SSNMR spectra with the transcriptomic data provided a complete picture of the major changes in the metabolic profile of soybeans in response to water deficiency. Copyright © 2017 John Wiley& Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…To account for the diversity of plant species, their evolving traits during growth, and the development of genetically modified organisms, statistical analysis approaches, more commonly undertaken in metabolomics and 1 H HR-MAS studies of natural products, begin to extend to ssNMR research of lignocellulose. For example, such strategies have been applied to monitor water deficiency effects in order to better understand drought stress on plants . Unfortunately, ssNMR lacks the time efficiency to survey a large number of samplesa mandatory step to match the success of metabolomics in solution NMR. , …”
Section: Solid-state Nmr Studies Of Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for the diversity of plant species, their evolving traits during growth, and the development of genetically modified organisms, statistical analysis approaches, more commonly undertaken in metabolomics and 1 H HR-MAS studies of natural products, begin to extend to ssNMR research of lignocellulose. For example, such strategies have been applied to monitor water deficiency effects in order to better understand drought stress on plants . Unfortunately, ssNMR lacks the time efficiency to survey a large number of samplesa mandatory step to match the success of metabolomics in solution NMR. , …”
Section: Solid-state Nmr Studies Of Plant Materialsmentioning
confidence: 99%
“…For example, such strategies have been applied to monitor water deficiency effects in order to better understand drought stress on plants. 332 Unfortunately, ssNMR lacks the time efficiency to survey a large number of samplesa mandatory step to match the success of metabolomics in solution NMR. 333,334 Since NMR resolves differences in chemical environments, changes that occur on biomaterials after they are subjected to any form of exterior physical or chemical perturbation can be easily detected using well-established chemical shifts, 335−337 with the assistance of an online chemical shift database.…”
Section: Polymer Contacts In Secondary Cell Wallsmentioning
confidence: 99%
“…An increasing number of studies are now using HRMAS NMR to better understand human daily food consumption. Published reports in this arena have included such topics as onion, 127 almonds, 128 grapes, 129 apples, 130 soybean, 131 and smart crops. 132,133 Of note, the results obtained from such studies now appear to be influencing the operations of certain food industries.…”
Section: Metabolomics Studies Of Plants and Foodmentioning
confidence: 99%
“…For instance, the study of soybean leaves grown with and without water-deficiency stress with HRMAS, revealed differences in the metabolite profiles. A total of 30 metabolites were identified, with the amino acid metabolites present in the metabolite profile of soybean leaves with water-deficient stress [ 129 ]. HRMAS can therefore aid in elucidating plant response mechanisms.…”
Section: 4ir Technologies and Plant Metabolomicsmentioning
confidence: 99%